PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPEGROUP INVESTIGATION (GI) UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR IPS SEJARAH PADA SISWA KELAS VIII B SMP PGRI 4 DENPASAR TAHUN PELAJARAN 2016/2017 - Rulianto Rulianto (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
The purpose of this research is to know the benefit of cooperative type study type study (GI) method in improving motivation of IPS learning History in grade VIII B students of SMP PGRI 4 Denpasar and to know the benefit of cooperative type study type study (GI) method in improving learning result of IPS History on grade VIII B students SMP PGRI 4 Denpasar The results showed that there is a real difference. Cooperative learning method type Group investigation (GI) can be applied to students of class VIII B SMP PGRI 4 Denpasar. this method can improve students' learning motivation. this is evident from the observation in the first cycle of meeting I reached 28, 21. meeting II 30.0 and meeting III reached 30.5, not only limited to the increase also occurred in cycle II At the meeting I where the result reached 31.39, II 34.17 and meeting III 35.25. see the results of observations that are obtained means the enthusiasm of students in following IPS learning becomes better by using model of learning model. Application of cooperative learning model Group Investigation (GI) can improve learning outcomes in students of grade VIII B SMP PGRI 4 Denpasar.This is seen in the improvement in terms of student learning outcomes that occur positively, meaning the enthusiasm of students in the process of instructional learning on the achievement of learning objectives and results of good student value, it is seen in the implementation of the stage that researchers do, where the cycle I to reach the average average 82.5%, absorption 82.5% and mastery learning reaches 72.5% and increases in cycle II to average 86.25%, absorption 82.25% and learning completeness reaches 100%. the increase in learning outcomes is inseparable from the students' ability to continue being taught at each meeting. hai is increasingly proves that the model of learning in applied to improve the spirit of learning in the subjects of IPS History, So it can be concluded that the model study group investigation can improve learning motivation and student learning outcomes.